Human-Robot Relationships in Millennial CGI Narratives: Ethical, Emotional, and Social Dimension - anggraini, indrani dewi; Sarah, Nani Nuraini (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
This study investigates the multifaceted dynamics of human-robot relationships as portrayed in contemporary CGI narratives. Focusing on millennial cinematic and digital content, it explores the ethical considerations, emotional engagements, and social implications of human interactions with robotic entities. By analyzing a selection of prominent CGI films and series, the research examines how these narratives address issues of autonomy, moral responsibility, and the emotional bonds formed between humans and robots. The study also considers the societal impact of these representations, including the potential for reshaping public perceptions and the ethical discourse surrounding artificial intelligence. The findings highlight the complex interplay between technology and humanity, offering insights into the evolving nature of human-robot interactions in modern storytelling.